Immersion between Semiotic Theories - Melnikova, Irina (Semiotika, 2022)
The paper focuses on the book of poetry immersion (2017) by Lithuanian poet Gytis Norvilas, maps the strategies of its reading within the framework of the semiotic-pragmatic approach, and considers the theoretical issues of the mapping. Despite the book cannot be unambiguously defined as an example of patterned poetry, it is configured in a specific way which exposes the functionality of the structural visual layer in written / printed poetry. This feature of the text in question inspires to revise the interpretation of the issue of iconicity and the configuration of the model of reading literature, proposed by the semiotic-pragmatic approach. The semiotic-pragmatic modelling combines Peircean and Jakobsonian ideas with minor insertions of Lotmanian thought (i.e. Johansen 2002), thus it links the ideas from the conceptual systems, based on different epistemological grounds (Peircean vs Saussurean notion of sign). It creates theoretical tensions that force to raise the question of how the transference of notions from one system to another changes their meaning, and where one could find the basis for overcoming or bypassing the controversies. The first part of the paper explores the theoretical tensions between Peircean, Jakobsonian and Lotmanian approaches to the issues of iconicity and attempts at revealing the fields of theoretical reasoning that help to define the ground of contradictions and see the way of their bypassing. Besides, it relates the discussion of iconicity with a discussion of the semiotic-pragmatic model of reading as iconization, based on the Jakobsonian idea of intersemiotic translation, and revises the model concerning the printed poetic text. The second part of the paper exemplifies the theoretical issues in the analysis of the book of poetry immersion. It examines the process of diagrammatization – the reading strategy, which makes the syntax of the text and that of the book the meaning-making devices, shows how diagrammatization semantizes the structure of the book, transforms the process of imaginization, and helps to identify the role of the book’s dialogue with hypotext to which both intertextual references and the structure of the text refer.